Furan measurement in transformer oil by UV-Vis spectroscopy using fuzzy logic approach - Lai, Sin Pin (Curtin University, 2009)
An Ultraviolet to Visible (UV-Vis) spectroscopic analysis based on fuzzy logic approach has been developed for furan content measurement in transformer oil. Following the successful identification and quantification of furan derivatives in transformer oil by ASTM D5837 standard, the new approach is able to approximate the furan content more conveniently and economically. As furan concentration level would determine the absorption intensity in UV-Vis spectral range, the fuzzy logic software model developed would exploit this characteristic to aggregate the furans content level in transformer oil. The UV-Vis spectral response at other ambient temperature is also studied. The proposed technique provides a convenient alternative to conventional method of furan measurement by High Performance Liquid Chromatography (HPLC) or Gas Chromatography Mass Spectrometry (GC/MS) in ASTM D5837 Standard.